2014
DOI: 10.1111/nph.12671
|View full text |Cite
|
Sign up to set email alerts
|

Verticillium transcription activator of adhesion Vta2 suppresses microsclerotia formation and is required for systemic infection of plant roots

Abstract: SummarySix transcription regulatory genes of the Verticillium plant pathogen, which reprogrammed nonadherent budding yeasts for adhesion, were isolated by a genetic screen to identify control elements for early plant infection.Verticillium transcription activator of adhesion Vta2 is highly conserved in filamentous fungi but not present in yeasts. The Magnaporthe grisea ortholog conidiation regulator Con7 controls the formation of appressoria which are absent in Verticillium species. Vta2 was analyzed by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(104 citation statements)
references
References 77 publications
1
92
0
Order By: Relevance
“…Although mutants can penetrate roots normally, subsequent root colonization is severely impaired and infection progress halted (60). It is not clear what role adhesion may play in pathogenesis, but Vta2 controls the expression of at least 275 genes, including a number of putative adhesins, virulence-associated effectors such as NLP2 and LysM, and, notably, the catalase-peroxidase gene CPX2, the product of which is secreted and needed for H 2 O 2 detoxification (60). Taken together, these results suggest that Vta2 may be responsible for activating fungal responses to host defenses (60).…”
Section: Distinct Pathways Control Responses To Nutrient Availabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Although mutants can penetrate roots normally, subsequent root colonization is severely impaired and infection progress halted (60). It is not clear what role adhesion may play in pathogenesis, but Vta2 controls the expression of at least 275 genes, including a number of putative adhesins, virulence-associated effectors such as NLP2 and LysM, and, notably, the catalase-peroxidase gene CPX2, the product of which is secreted and needed for H 2 O 2 detoxification (60). Taken together, these results suggest that Vta2 may be responsible for activating fungal responses to host defenses (60).…”
Section: Distinct Pathways Control Responses To Nutrient Availabilitymentioning
confidence: 99%
“…A corresponding adhesion control pathway in Verticillium has not yet been described, but Vta2 is clearly required for pathogenicity of strain JR2 on tomato. Although mutants can penetrate roots normally, subsequent root colonization is severely impaired and infection progress halted (60). It is not clear what role adhesion may play in pathogenesis, but Vta2 controls the expression of at least 275 genes, including a number of putative adhesins, virulence-associated effectors such as NLP2 and LysM, and, notably, the catalase-peroxidase gene CPX2, the product of which is secreted and needed for H 2 O 2 detoxification (60).…”
Section: Distinct Pathways Control Responses To Nutrient Availabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The MAPK kinase Msb2 and MAPK Hog1 (Wang et al, unpublished data) are important for microsclerotia formation and virulence in V. dahliae. Furthermore, genes encoding transcriptional regulators with important roles in virulence and development have also been characterized in this fungus (Santhanam and Thomma, 2013;Tran et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It was also confirmed that VDH1, encoding a class II hydrophobin, is involved in the formation of microsclerotia (Klimes et al 2008;Klimes and Dobinson 2006). In addition, many genes have been characterized that are involved in signal transduction pathways and regulation of microsclerotia formation of V. dahliae, such as VMK1, encoding a mitogen-activated protein kinase (Rauyaree et al 2005), VdGARP1, encoding a glutamic acid-rich protein , the G protein β subunit (named as VGB) (Tzima et al 2012), Vta2, encoding a nuclear zinc finger protein, (Tran et al 2014), the MADS-box transcription factor VdMcm1 , the mitogen-activated protein kinase (MAPK) Hog1 , and the MAPK Msb and Pbs2 Tian et al 2016). Unravelling the functional characterizations of these genes provides insight into the genetic control of microsclerotia formation in V. dahliae.…”
Section: Disease Cycle Of Verticillium Wilt Of Treesmentioning
confidence: 99%